The Mapping of Elementary School Teachers' Pedagogical Knowledge - Lalu Hamdian Affandi; Heri Hadi Saputra; Husniati Husniati (Indonesian Publication Center, 2020)
The aim of this research is to explore elementary school teachers’ pedagogical knowledge based on students’ perception. To achieve above aim, the research carried out by survey design with questionnaire as data collecting tool. Subjects of this research are 43 teachers selected conveniently. This study found that most of elementary school teachers have socio-cognitive pedagogical knowledge (44.18%), whereas the others 27.91% hold behavioristic and constructivistic views. Based on those results, it can be predicted that learning activities in elementary school classrooms will mostly occurred in a more communicative ways in which student builds the meaning based on their discussion about the topics in hand. This research suggests for further investigation to test effect of teacher’s pedagogical knowledge on students’ learning, such as their academic achievement, their social skills, and their subjective well-being.